Satisfaction of combined and exclusive injectable contraceptive users of progestogen and associated factors - Ana Gesselena da Silva Farias; Adman Câmara Soares Lima; Raquel Ferreira Gomes Brasil; Maria da Conceição dos Santos Oliveira Cunha; Glória Maria Almeida Oliveira; Escolástica Rejane Ferreira Moura (Rev Rene)
Objective: to know the satisfaction of users of injectable contraceptives with the methods; identify side effects related to the use and verify association between satisfaction and socio demographic variables, specifications of the injectable contraceptives and side effects. Methods: a cross-sectional study of 52 injectable contraceptives users filling a form. Results: 40 (76.9%) users reported being satisfied with the injectable contraceptives and 12 (23.1%) were dissatisfied. Type of injectable contraceptive and continuity of use were associated with users’ satisfaction (p = 0.042 and p <0.001, respectively); the most frequent side effects were weight gain (32.6%), amenorrhea (30.7%), headache (28.8%), hypo menorrhea (25.0%), nausea (25.0%) and hyper menorrhea15.3%). There was no association between satisfaction and socio demographic variables and side effects, however, users who presented weight gain, amenorrhea, headache, nausea and hyper menorrhea were more dissatisfied. Conclusion: the satisfaction of the user with injectable contraceptives varies with the type of the method and positively influences the continuity of use.